On racial icons : blackness and the public imagination - Fleetwood, Nicole R. (Pinpoints (Series), 2015)
Explores visual culture and race in the United States, focusing in particular on the significance of photography to document black public life. Examines America's fascination with representing and seeing race in a myriad of contexts as emblematic of national and racial progress at best, or as a gauge of a collective racial wound.